Acoustic Investigation of the Aperture Dynamics of an Elastic Membrane Closing an Overpressurized Cylindrical Cavity - Melo-Hurtado, F (Springer Verlag, 2015)
We report an experimental study of the acoustic signal produced by the rupture of an elastic membrane that initially closes a cylindrical overpressurized cavity. This configuration has been recently used as an experimental model system for the investigation of the acoustic emission from the bursting of elongated gas bubbles rising in a conduit. Here, we investigate the effect of the membrane rupture dynamics on the acoustic signal produced by the pressure release by changing the initial tension of the membrane. The initial overpressure in the cavity is fixed at a value such that the system remains in the linear acoustic regime. For large initial membrane deformation, the rupture time τrup is small compared to the wave propagation time in the cavity and the pressure wave inside the conduit can be fully captured by the linear theory. For low membrane tension, a hole is pierced in the membrane but its rupture does not occur. For intermediate deformation, finally, the rupture progresses in two steps: first the membrane opens slowly; then, after reaching a critical size, the rupture accelerates. A transversal wave is excited along the membrane surface. The characteristic signature of each opening dynamics on the acoustic emission is described. © 2015, Società Italiana di Fisica and Springer-Verlag Berlin Heidelberg.